Methodological guidance for studio design: A way of encouraging the development of design thinking - Mgr. art. Zuzana Turlíková, ArtD.; Mgr. art. Zuzana Pergerová; Mgr. art. Zuzana Pergerová (Architecture Papers of the Faculty of Architecture and Design STU, 2020)
Professional work experience with international internships of doctoral students and the goodwill of senior pedagogues to provide space for the next generation made it possi-ble to conduct several pedagogical experiments at the Faculty of Architecture and Design STU in Bratislava. One of them is the implementation and testing of Design Thinking tools based on principles of University of Stanford d.school that has been part of the subject Studio Tutorial since 2017. The aim is to assist with the design process and to support the development of innovative and critical thinking so that students are better prepared for the future job market in the context of the 4th Industrial Revolution. Tested methodology is certainly not the only choice. However, the basic principles follow pretty much the phases of the design process typical of the Vertical Studios at the Institute of Design at the Faculty. The process of design thinking is directly based on the human-centred approach. The presented pedagogical experiment has also focused on reflecting students' needs in order to prepare them better for their future professional career and has included different methods aimed at supporting team work and enhancing interdisciplinary cooperation. This article also includes feedback provid-ed by both students and pedagogues. In the circumstances of pandemic-struck year of 2020, the whole course has been taught in online environment, which has brought new challenges.